Penetapan Batas Luas Maksimum Penggunaan Lahan Untuk Usaha Perkebunan Kelapa Sawit : Pendekatan Analisis Sistem dan Analytical Network Process (ANP) - Bayu Kharisma; Mahra Arari Heryanto; Adi Nugraha (Trunojoyo University of Madura, 2020)
This paper aims to analyze whether or not the extent of maximum land use for oil palm plantations is needed or not based on efficiency and equity aspects, considering that the commodity is a national strategic superiority. The methodology used in this study is System Dynamics and Analytical Network Process (ANP) for the Implementation of the Maximum Extent of Land Use for Oil Palm Plantation Businesses. Based on the system analysis approach, it can be identified that the determination of the maximum extent of land use in the oil palm plantation business must pay attention to the principles of fairness, efficiency principles and regulations and policies. The results of ANP calculations that the alternative policy that is a priority based on expert perceptions is the need to limit the extent of land use. Meanwhile, experts agree or accordingly that the limitations on the maximum extent of land use in oil palm plantation businesses in Indonesia are the most influential policy alternatives compared to not needing to be limited.